Implementation of Change Management Through the Adkar Method in the Development of Export Marketing at PT Agritek Desa Indonesia - Darmawansyah, Muhamad Adjie; Yunizar, Yunizar (Jurnal Multidisiplin Indonesia, 2024)
Change management is a structured effort to increase the flexibility and adaptability of an organization when facing continuous changes. The Micro, Small and Medium Enterprises (MSME) sector has a vital role in the Indonesian economy in the era of globalization to be able to make changes in the export context. This research aims to solve the problem of developing an export marketing strategy at PT Agritek Desa Indonesia for its product, namely ChipsyChips, to increase production through marketing by implementing the ADKAR method. The research results show that PT Agritek Desa Indonesia is able to make changes to its export marketing development activities through the ADKAR method, which consists of awareness of marketing products on global marketplace platforms and creating content on social media, the desire to have an effective marketing strategy, namely implementing the STP method, getting knowledge regarding the features on the Alibaba platform, being able to utilize the Alibaba platform to market products, and increasing reinforcement in marketing activities through content containing positive reviews from buyers of ChipsyChips products.